2010
DOI: 10.1111/j.1551-2916.2010.04282.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Na+, SiO44−, and CO32−Co-Substituted Hydroxyapatite

Abstract: The mechanism of Na+, SiO44−, and CO32− cosubstitution in hydroxyapatite (HAP) crystal structure was investigated. Several powders were prepared by wet chemical precipitation at 37°C in the presence of different concentrations of sodium silicate in open atmosphere. The powders were characterized using chemical analysis, scanning electron microscopy, X‐ray diffraction, and Fourier‐transform infrared spectrometry spectroscopy. Increasing of silicate ions substitutions were associated with increasing of carbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…[64] After 30 min of activation, a single-phase product forms; the only phase present in the sample is the apatite phase identical to that reported in the literature. [21,24] Rietveld refinement shows that the synthesized silicate-substituted apatite has the following lattice parameters: a = 9.403(2) Å and c = 6.923(2) Å. The crystallite size of the synthesized product is 20 nm.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…[64] After 30 min of activation, a single-phase product forms; the only phase present in the sample is the apatite phase identical to that reported in the literature. [21,24] Rietveld refinement shows that the synthesized silicate-substituted apatite has the following lattice parameters: a = 9.403(2) Å and c = 6.923(2) Å. The crystallite size of the synthesized product is 20 nm.…”
Section: Resultsmentioning
confidence: 97%
“…[22,24] Apatite modified with silicate ions can be obtained by several methods, namely, the sol-gel method, [28,29] hydrothermal synthesis, [12,30,31] solid-state ceramic synthesis, [32,33] and the aqueous (wet) precipitation method. [11,16,[20][21][22]24] The latter is the most widely used; the synthesis is realized by precipitation from phosphate salt solutions and calcium salts or by performing a reaction between phosphoric acid, a calcium hydroxide suspension, and soluble silicon compounds. It should be noted that the properties of the products obtained by different authors by the same method can differ considerably, even if the same reactants are used.…”
Section: Introductionmentioning
confidence: 99%
“…The HA and Se-HA powders were prepared by an aqueous co-precipitation method [20]. Briefly, the precipitation was carried out in a three-neck bottle at open atmosphere and in an oil-bath of 80°C.…”
Section: Methodsmentioning
confidence: 99%
“…The most accepted hypothesis is that areas of stress in the crystal lattice caused by the insertion of a substituent can be compensated for by the insertion of other ions of different sizes and charges. Some studies have shown that ions easily found during the precipitation of apatites in aqueous media, such as Na + , Cl − and CO 3 2− , can thermally stabilize the apatitic phase in association with other doping elements [25,26].…”
Section: Introductionmentioning
confidence: 99%